Bigeminy with Prolonged QT Interval as an Ominous Sign for Impending Torsades de Pointes: A Case Report - Thuc Vu; Jake Valentine (Clinical Practice and Cases in Emergency Medicine)
Introduction: Ventricular ectopic beats and corrected QT interval (QTc) prolongation are both relatively common entities that are typically benign. It is difficult to predict subsequent dysrhythmias from either electrocardiogram (ECG) feature. The combination of both features may better predict the risk of torsades de pointes. We highlight a case of torsades preceded by a bizarre bigeminal rhythm with QTc prolongation likely caused by memantine use and hypokalemia. Case Report: An 84-year-old female presented to the emergency department with a fall. A syncope workup revealed an ECG demonstrating bigeminy with a prolonged QTc interval. Several minutes after obtaining the ECG, the patient went into torsades. She had multiple subsequent cardiac arrests during the rest of her hospital stay. This case report details the importance of recognizing ventricular bigeminy in the context of QTc prolongation as a harbinger of torsades. Conclusion: While premature ventricular contractions including bigeminy may be a benign finding, when accompanied by prolonged QTc intervals, they warrant immediate investigation and treatment of potential underlying pathology to prevent torsades and subsequent cardiac arrest.